MicroRNAs in the DNA Damage/Repair Network and Cancer - Alessandra Tessitore; Germana Cicciarelli; Filippo Del Vecchio; Agata Gaggiano; Daniela Verzella; Mariafausta Fischietti; Davide Vecchiotti; Daria Capece; Francesca Zazzeroni; Edoardo Alesse (International Journal of Genomics)
Cancer is a multistep process characterized by various and different genetic lesions which cause the transformation of normal cells into tumor cells. To preserve the genomic integrity, eukaryotic cells need a complex DNA damage/repair response network of signaling pathways, involving many proteins, able to induce cell cycle arrest, apoptosis, or DNA repair. Chemotherapy and/or radiation therapy are the most commonly used therapeutic approaches to manage cancer and act mainly through the induction of DNA damage. Impairment in the DNA repair proteins, which physiologically protect cells from persistent DNA injury, can affect the efficacy of cancer therapies. Recently, increasing evidence has suggested that microRNAs take actively part in the regulation of the DNA damage/repair network. MicroRNAs are endogenous short noncoding molecules able to regulate gene expression at the post-transcriptional level. Due to their activity, microRNAs play a role in many fundamental physiological and pathological processes. In this review we report and discuss the role of microRNAs in the DNA damage/repair and cancer.